The Detrimental Effects of Kynurenine, a Tryptophan Metabolite, on Human Bone Metabolism - Kim, Beom-Jun (J Clin Endocrinol Metab, 2019)
CONTEXT: Studies in aged mice support a role for kynurenine, a tryptophan metabolite, in age-induced bone loss; however, the role of kynurenine in human bone metabolism is not well understood. OBJECTIVE: To assess whether the kynurenine level in bone marrow (BM) aspirates, directly reflecting the bone microenvironment, is associated with osteoporosis-related phenotypes and bone biochemical markers. DESIGN AND SETTING: A case-control study conducted in a clinical unit. PARTICIPANTS AND MAIN OUTCOME MEASURES: BM samples were collected from 72 patients at the time of hip surgery for either fragility hip fracture (HF) (n = 27) or for other causes (n = 45). In these samples, kynurenine was measured by liquid chromatography–tandem mass spectrometry, and the levels of tartrate-resistant acid phosphatase 5b (TRAP5b), bone-specific alkaline phosphatase (BSALP), receptor activator of nuclear factor-κB ligand (RANKL), and osteoprotegerin (OPG) were measured by immunoassay. RESULTS: Age was positively correlated with BM kynurenine level. After adjustment for confounders, subjects with fragility HF had a 39.7% higher BM kynurenine level than those without, and the OR per SD increment in BM kynurenine level for fragility HF was 3.80. The BM kynurenine level was inversely associated with bone mass at the total femur. Higher kynurenine concentrations were significantly associated with higher TRAP-5b and RANKL levels, but not with BSALP and OPG levels, in BM plasma. CONCLUSION: These results suggest that increased kynurenine levels during aging may contribute to the bone fragility seen in the elderly through increased bone resorption, with a resultant imbalance in bone remodeling.